2012
DOI: 10.1166/jnn.2012.5411
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Production of Hydrogen from Water Using Microporous Porphyrin Coordination Lattices

Abstract: In this study, we investigated the photochemical production of hydrogen from water using bio-inspired heterogeneous microporous porphyrin coordination lattices (PCLs), [Ru2(MTCPP)BF4] (M = H2 (PCL-1), Zn (PCL-2); TCPP = Tetrakis(4-carboxyphenyl)porphyrin), under visible (380 nm <) and UV (320 nm <) light irradiations. In the presence of Na2EDTA (as a sacrificial donor) and MV2+ (methyl-vilologen; as a electron relay), PCLs exhibits photocatalytic activity for hydrogen evolution; the maximum amounts of turnover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…All photochemical reactions were performed in a closed gas circulation system with a Pyrex reaction cell. , The reaction solution (10 cm 3 ) containing TEA (0.36 mol/dm 3 , pH ∼ 10–11) and Ti 3 NS:Rh­( x ) or Rh­( x ) - Ti 3 NS colloidal suspension (1 mg) was degassed by repeated freeze pump–thaw cycles. The reaction solution was shifted into the reaction vessel with a glovebox under an Ar-saturated atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…All photochemical reactions were performed in a closed gas circulation system with a Pyrex reaction cell. , The reaction solution (10 cm 3 ) containing TEA (0.36 mol/dm 3 , pH ∼ 10–11) and Ti 3 NS:Rh­( x ) or Rh­( x ) - Ti 3 NS colloidal suspension (1 mg) was degassed by repeated freeze pump–thaw cycles. The reaction solution was shifted into the reaction vessel with a glovebox under an Ar-saturated atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The essence of the closed circulatory system was described in the Supporting Information. Preparation and measurements were performed in the same manner as described elsewhere . For each measurement, it was used that 50 mg of the samples, 10 ml of water and 558 mg of EDTA‐2Na, which acted as the sacrificial reagent.…”
Section: Methodsmentioning
confidence: 99%
“…357 Other porphyrin diruthenium-based MOF materials were reported by Mori and co-workers as photocatalysts for H 2 evolution. 358 Because Ru and Fe are in the same group and share similar chemical properties, these porphyrin dirutheniumbased MOF complexes are discussed in this subsection. Photocatalytic studies showed relatively low activity.…”
Section: Chemical Reviewsmentioning
confidence: 99%